Teacher training in Media Education: an experience with 150 teachers in Portugal - Tomé, V. (Society for Information Technology & Teacher Education International Conference 2011, 2011)
We are going to present the results from a course called ‘School Newspaper and Media Education in the Promotion of Reading and Writing’, certified by the Educational-Teaching Council of Continuing Education, which occurred between January and July 2010, in Portugal. The course involved 150 teachers, from pre-school to secondary level. Technology resources were used on the course, which had been produced and tested in the ‘Media Education in the Castelo Branco District (2007/2010)’ project, financed by the Portuguese Science and Technology Foundation. Among the resources is the dvd ‘We’re going to make a school newspaper’, an on-line platform for the publication of school newspapers, and also a support manual for teachers. The course was mainly practical, in that the teachers developed Media Education activities with their students, and afterwards thought about these activities and produced a report. As a result of this course a good-practice manual is being arranged.